Prevalence and Factors Associated with Tobacco Use among High School Students - KC, Bhakta Bahadur; Khanal, Pratik; Oli, Laxmi Kumari; Dhital, Shalik Ram; Pradhan, Bandana; Pahari, Durga Prasad; Paudel, Keshav Raj (Journal of Nepal Health Research Council, 2022)
Background: Tobacco use is the leading cause of morbidity and mortality worldwide. Tobacco use among school-level students is a growing a public health problem in Nepal. A number of factors may be associated with tobacco use, but there is lack of literature showcasing an in-depth understanding of the growing prevalence of tobacco use in the Nepalese context. Therefore, our study aims to determine the prevalence of tobacco use and examine the factors associated with tobacco use among high school students at public schools in Budhanilkantha municipality, Kathmandu, Nepal. Methods: A cross-sectional survey was conducted, and 378 students were selected for this study. The schools were selected randomly. Data collection was carried out using the self-administered questionnaires adapted from the World Health Organization used Global Youth Tobacco Survey and the Center for Disease Control and Prevention used Youth Tobacco Survey.Results: Overall, 31.7% of the students ever consumed any tobacco products, and 20.1% were current tobacco users. One in five students started smoking when they were less than ten years of age. The proportion of students seeing at least one family member smoking and using smokeless tobacco was 52.1% and 47.1% respectively. Male and older students were significantly more likely to consume tobacco products than female and young students.Conclusions: This study showed that a significant proportion of school students had experienced tobacco use. Age and sex of the students were significantly associated with the status of current smoking and the use of smokeless tobacco.Keywords: Nepal; school; students; tobacco use